Highway engineering handbook : building and rehabilitating the infrastructure - Boedecker, Kenneth, Jr. (New York : McGraw Hill Education, 1996)
This comprehensive handbook compiles the full scope of information necessary for effective and cost conscious contemporary highway design. The contributing engineers review environmental issues, location, design, traffic, pavement design and rehabilitation, bridge engineering, culvert design, signing, lighting and life cycle costs, as well as present special discussions on the selection and design of retaining walls to reduce traffic noise and screen unsightly areas. Includes illustrations, maps, graphs and tables.
Table of Contents Environmental Issues Highway Location, Design, and Traffic Pavement Design and Rehabilitation Bridge Engineering Culverts, Drainage, and Bridge Replacement Safety Systems Signing and Roadway Lighting Signing Roadway Lighting Retaining Walls Noise Walls Value Engineering and Life Cycle Cost
Includes bibliographical references and index.
Keywords: HIGHWAY ENGINEERING-- UNITED STATES -- HANDBOOKS, MANUALS, ETC